2018
DOI: 10.3390/e20030196
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time ECG-Based Detection of Fatigue Driving Using Sample Entropy

Abstract: In present work, the heart rate variability (HRV) characteristics, calculated by sample entropy (SampEn), were used to analyze the driving fatigue state at successive driving stages. Combined with the relative power spectrum ratio β/(θ + α), subjective questionnaire, and brain network parameters of electroencephalogram (EEG) signals, the relationships between the different characteristics for driving fatigue were discussed. Thus, it can conclude that the HRV characteristics (RR SampEn and R peaks SampEn), as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 52 publications
3
51
0
Order By: Relevance
“…52 In the study of nerve activity, the synchronization algorithms for network reconstruction were effectively used. 53,54 In our study, the activities of the neuronal clusters suppressed when a driver was in a state of mental fatigue. At this time, their activities were relatively consistent.…”
Section: Previous Studiesmentioning
confidence: 55%
“…52 In the study of nerve activity, the synchronization algorithms for network reconstruction were effectively used. 53,54 In our study, the activities of the neuronal clusters suppressed when a driver was in a state of mental fatigue. At this time, their activities were relatively consistent.…”
Section: Previous Studiesmentioning
confidence: 55%
“…Whereas in [28], the authors used non-visuals EEG signals to develop the DDD system. The EEG signals were also used in paper [20] to detect fatigue. In that study, the authors used a combined approach of SVM and deep-learning algorithms.…”
Section: Related Workmentioning
confidence: 99%
“…Research by Stam and Reijneveld showed that the modern complex network theory was widely used to simulate human brain function [35]. Some studies have proved that the brain network connection could effectively express brain function and related neural activities [36][37][38][39][40]. In this paper, the authors use the brain network features to recognize eye movements.…”
Section: Introductionmentioning
confidence: 99%